2016
DOI: 10.1016/j.orhc.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Linear formulation for the Maximum Expected Coverage Location Model with fractional coverage

Abstract: a b s t r a c tSince ambulance providers are responsible for life-saving medical care at the scene in emergency situations and since response times are important in these situations, it is crucial that ambulances are located in such a way that good coverage is provided throughout the region. Most models that are developed to determine good base locations assume strict 0-1 coverage given a fixed base location and demand point. However, multiple applications require fractional coverage. Examples include stochast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The second most addressed problem type was spatial analysis, which represents 32.74% of the papers. All the studies that performed some level of descriptive analysis, inference, or observation of spatial properties of events used [13], [44], [45], [47]- [50], [52]- [55], [60], [64], [65], [76], [78], [80]- [91], [95]- [97], [101], [102], [104], [107]- [109], [111]- [115], [117], [118], [121], [126], [138], [143]- [148], [150]- [152], [155], [157], [159], [161], [163], [166]- [171], [174]- [184], [186], [192], [196], [198], [199] Spatial analysis 55 32.74% [11],…”
Section: A Problem Type Findingsmentioning
confidence: 99%
“…The second most addressed problem type was spatial analysis, which represents 32.74% of the papers. All the studies that performed some level of descriptive analysis, inference, or observation of spatial properties of events used [13], [44], [45], [47]- [50], [52]- [55], [60], [64], [65], [76], [78], [80]- [91], [95]- [97], [101], [102], [104], [107]- [109], [111]- [115], [117], [118], [121], [126], [138], [143]- [148], [150]- [152], [155], [157], [159], [161], [163], [166]- [171], [174]- [184], [186], [192], [196], [198], [199] Spatial analysis 55 32.74% [11],…”
Section: A Problem Type Findingsmentioning
confidence: 99%
“…It then becomes necessary to model the fact that helicopters are sometimes unavailable, which can be done by including a predetermined busy fraction . This has been demonstrated in both a model for efficiency [ 28 ] and a model for fairness [ 14 ]. Note that due to the large rural-urban differences in Norway, it is unclear whether a busy fraction model is appropriate, and modelling HEMS unavailability remains a topic for careful consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ambulances must be present at a particular time and distance to the requested location [10], and EMS planners should choose the best sites for establishing and deploying ambulances [11]. Researchers have found that significant deviations from these standards can worsen patients' conditions [12]. The present study is an applied-developmental study and has used cross-sectional data of the Emergency Organization in East Tehran in 2018.…”
Section: Methodsmentioning
confidence: 99%
“…One of these efficient models is the Double Standard Model (DSM), used to optimize and improve the location of ambulance services in Belgium [10], Canada [11], and Austria [12]. It is one of the accepted models for related issues is locating an ambulance [13].…”
Section: Introductionmentioning
confidence: 99%